An IgG‐based bispecific antibody for improved dual targeting in PSMA‐positive cancer - Latifa Zekri; Fabian Vogt; Lukas Osburg; Stefanie Müller; Joseph Kauer; Timo Manz; Martin Pflügler; Andreas Maurer; Jonas S Heitmann; Ilona Hagelstein; Melanie Märklin; Sebastian Hörner; et al. (EMBO Molecular Medicine)
Abstract The prostate‐specific membrane antigen (PSMA) has been demonstrated in numerous studies to be expressed specifically on prostate carcinoma cells and on the neovasculature of several other cancer entities. However, the simultaneous expression of PSMA on both, tumor cells as well as tumor vessels remains unclear, even if such “dual” expression would constitute an important asset to facilitate sufficient influx of effector cells to a given tumor site. We report here on the generation of a PSMA antibody, termed 10B3, which exerts superior dual reactivity on sections of prostate carcinoma and squamous cell carcinoma of the lung. 10B3 was used for the construction of T‐cell recruiting bispecific PSMAxCD3 antibodies in Fab‐ and IgG‐based formats, designated Fabsc and IgGsc, respectively. In vitro, both molecules exhibited comparable activity. In contrast, only the larger IgGsc molecule induced complete and durable elimination of established tumors in humanized mice due to favorable pharmacokinetic properties. Upon treatment of three patients with metastasized prostate carcinoma with the IgGsc reagent, marked activation of T cells and rapid reduction of elevated PSA levels were observed.